1927 Conn. Acts 4286 - (:unkn) unknown (My University, 1927)
An Act Concerning The Use of Shot Guns on Sundays by Members of Gun Clubs, ch. 214: Extended § 67 of chapter 222 of 1923 Conn. Pub. Acts to apply to gun clubs affiliated with the NRA and members of such gun clubs using shot guns. The extension restricts the use of shotguns at rifle ranges on Sundays to the hours of one and six in the afternoon. Does not allow hunting on Sundays.
Keywords: SHOOTING RANGES OR GALLERIES